Pengaruh Kualitas Pelayanan Dan Harga Terhadap Kepuasan Pelanggan Pada Minimarket We Mart Kota Padang - Zaki (CV. ITTC INDONESIA, 2024)
This research is entitled The Influence of Service Quality on Customer Satisfaction at the We Mart Minimarket in Padang City. The reason behind the author's choice of this title is that We Mart is a minimarket that is open 24 hours. Basically, it is rarely found in Padang City which serves 24 hours, so the service and prices are one of the determining factors for customer satisfaction when shopping there, in this research using primary data by distributing questionnaires to customers who shop there. The research results show that the variables of service quality and price have a significant effect on customer satisfaction, both partially and simultaneously.